Prevalence of ESBL-Producing Enterobacter Species Resistant to Carbapenems in Iran: A Systematic Review and Meta-Analysis - Farzad Khademi; Hamid Vaez; Zohreh Neyestani; Amirhossein Sahebkar (International Journal of Microbiology)
Background. Carbapenems are the last-line therapy for multidrug-resistant (MDR) infections caused by Enterobacterales, including those caused by Enterobacter species. However, the recent emergence of carbapenem-resistant (CR) and extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae pathogens, which are resistant to nearly all antibiotics, has raised concerns among international healthcare organizations. Hence, because there is no comprehensive data in Iran, the current study aimed to evaluate the prevalence of antibiotic resistance among Enterobacter species, especially CR and ESBL-producing strains, in Iran. Methods. The literature search was performed up to June 21, 2021, in national and international databases using MeSH-extracted keywords, i.e., Enterobacter, antibiotic resistance, carbapenem, ESBL, and Iran. Study selection was done based on the predefined inclusion and exclusion criteria, and data analysis was carried out using the Comprehensive Meta-Analysis (CMA) software. Results. The pooled prevalence of Enterobacter species resistant to various antibiotics is as follows: imipenem 16.6%, meropenem 16.2%, aztreonam 40.9%, ciprofloxacin 35.3%, norfloxacin 31%, levofloxacin 48%, gentamicin 42.1%, amikacin 30.3%, tobramycin 37.2%, tetracycline 50.1%, chloramphenicol 25.7%, trimethoprim/sulfamethoxazole 52%, nalidixic acid 49.1%, nitrofurantoin 43%, ceftriaxone 49.3%, cefixime 52.4%, cefotaxime 52.7%, ceftazidime 47.9%, cefepime 43.6%, and ceftizoxime 45.5%. The prevalence rates of MDR and ESBL-producing Enterobacter species in Iran were 63.1% and 32.8%, respectively. Conclusion. In accordance with the warning of international organizations, our results revealed a high prevalence of ESBL-producing Enterobacter species in Iran, which is probably associated with the high prevalence of Enterobacter species resistant to most of the assessed antibiotics, especially MDR strains. However, the resistance rate to carbapenems was relatively low, and these drugs can still be considered as drugs of choice for the treatment of Enterobacter infections in Iran. Nevertheless, continuous monitoring of drug resistance along with antibiotic therapy based on the local data and evaluation of the therapeutic efficacy of new antibiotics or combination therapeutic strategies, such as ceftazidime/avibactam, meropenem/vaborbactam, plazomicin, and eravacycline, is recommended.